An updated meta-analysis of device related thrombus following left atrial appendage closure in patients with atrial fibrillation - Zhang, Song; Xiong, Si-huai; Guan, Yu-gen; Zhao, Xian-xian; Qin, Yong-wen; Guo, Zhi-fu; Bai, Yuan (Frontiers in Cardiovascular Medicine, 2022)
Aims: Device related thrombus (DRT) is a known complication of left atrial appendage closure (LAAC). However, the relation between DRT and elevated risk of ischemic events remains controversial. This study is sought to reassessed the incidence of DRT following LAAC and the relation between DRT and elevated risk of ischemic stroke and systemic embolism (SE) with latest clinical trials included. Methods: The PubMed, Embase, and Cochrane Library databases were systematically searched from their inception until April 2022 for studies that reported the incidence of DRT and compared the incidence of both stroke and SE between DRT patients and non-DRT patients. Results: In 59 eligible studies, the incidence of DRT was 366/12,845 (2.8%, ranging from 0% to 11%, I2 = 64%). The incidence of DRT was not statistically different between single-seal device (SS) and dual-seal device (DS) in subgroup analysis (171/6,190 [2.8%] vs. 78/3,023 [3.6%]; p = 0.93). The pooled incidence of stroke (26 studies, 7,827 patients) in patients with and without DRT was 11.5% in DRT patients and 2.9% among non-DRT patients (OR: 5.08; 95% CI = 3.47-7.44). In the sensitivity analysis, DRT was associated with higher rate of stroke (12.1% vs. 3.2%; OR: 4.14; 95% CI = 2.69-6.38) and SE (16.0% vs. 3.8%; OR: 4.48; 95% CI = 3.04-6.62). Conclusion: The incidence of DRT was low and similar between SS and DS devices. DRT was associated with increased rates of ischemic events. The occurrence rate of ischemic events associated DRT was comparable between two occlusion mechanism devices.